Literasi Digital Calon Pekerja Indonesia dan Self-control dalam Berbagi Konten Digital - Eka Widi Astuti (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2023)
Hundreds of CPMI who are victims of hoaxes on overseas job opportunities can be found easily on online news. This study aims to measure the effect of digital literacy competence and understanding the credibility of information on self-control in sharing digital content, especially related to overseas job opportunities. The research method is an explanatory survey of 699 CPMI West Java with 3.5 % of MoE. There are two main conclusions, that is: 1) West Java’s CPMI digital literacy index is at the level of proficiency level 6 with the advanced category, and 2) digital literacy and CPMI's understanding of the information credibility has a positive effect on the level of self-control of CPMI in sharing digital information. The hoaxes about overseas job opportunities should be resolved from the upstream side of the problem, such as by increasing digital literacy competencies evenly among CPMI. This effort can be collaborated through various government’s work programs such as dissemination, counseling, or multi-level training.